Shroom3 contributes to the maintenance of the glomerular filtration barrier integrity - Yeo, Nan Cher; O’Meara, Caitlin C.; Bonomo, Jason A.; Veth, Kerry N.; Tomar, Ritu; Flister, Michael J.; Drummond, Iain A.; Bowden, Donald W.; Freedman, Barry I.; Lazar, Jozef; Link, Brian A.; Jacob, Howard J. (Genome Research, 2015)
Genome-wide association studies (GWAS) identify regions of the genome correlated with disease risk but are restricted in their ability to identify the underlying causative mechanism(s). Thus, GWAS are useful “roadmaps” that require functional analysis to establish the genetic and mechanistic structure of a particular locus. Unfortunately, direct functional testing in humans is limited, demonstrating the need for complementary approaches. Here we used an integrated approach combining zebrafish, rat, and human data to interrogate the function of an established GWAS locus (SHROOM3) lacking prior functional support for chronic kidney disease (CKD). Congenic mapping and sequence analysis in rats suggested Shroom3 was a strong positional candidate gene. Transferring a 6.1-Mb region containing the wild-type Shroom3 gene significantly improved the kidney glomerular function in FHH (fawn-hooded hypertensive) rat. The wild-type Shroom3 allele, but not the FHH Shroom3 allele, rescued glomerular defects induced by knockdown of endogenous shroom3 in zebrafish, suggesting that the FHH Shroom3 allele is defective and likely contributes to renal injury in the FHH rat. We also show for the first time that variants disrupting the actin-binding domain of SHROOM3 may cause podocyte effacement and impairment of the glomerular filtration barrier.
10.1101/gr.182881.114